PENINGKATAN HASIL BELAJAR IPS SISWA DENGAN MENGGUNAKANMETODE LATIHAN DI KELAS IV SD NEGERI 006 TRI MULYA JAYAKECAMATAN UKUI - Ngadimin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is a classroom action research motivated by the low learning outcomes of fourth-grade social studies (IPS) students at SD Negeri 006 Tri Mulya Jaya, Ukui District. The study was conducted in two cycles by applying the exercise method. The data used in this study consisted of teacher activity data, student activity data, and students’ social studies learning outcomes. The results showed that teacher and student activities, as well as learning outcomes in social studies, improved after the implementation of the actions. This improvement is evidenced by: (a) teacher activity, which increased from a score of 19 (63.00%) in the first cycle, categorized as quite good, to a score of 22 (73.00%) in the second cycle, categorized as good; (b) student activity, which increased from a score of 47 (60.00%) in the first cycle, categorized as high, to a score of 52 (67.00%) in the second cycle, also categorized as high; and (c) social studies learning outcomes, in which students achieving scores equal to the minimum mastery criterion (KKM) within the interval of 65–74 increased from 7 students (54.00%) in the first cycle to 8 students (62.00%) in the second cycle, while students achieving high scores within the interval of 75–84 remained at 3 students (23.00%) in both cycles. Overall, the number of students who achieved the KKM increased from 10 students (77.00%) in the first cycle to 11 students (85.00%) in the second cycle.